Menggali Koneksi: Dialog Antar Generasi dalam Memahami Milenial - Maulana Laksana Putra; Abdee Wahyu Hertaliando; Danendra Putra Hermawan; Dyadra Tsaafiek Pindho Resi; Radya Adhi Pratama; Masduki Asbari (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
In the article entitled Intergenerational Dialogue to Understand Millennial Humans, it explains the importance of understanding what humans are. Understanding Humans is an individual's positive attitude that enables him to develop a positive assessment, both of himself and of the environment or situation he is facing. The text does not explicitly mention the existence of research conducted by the author. We can see that the text is a narrative or personal reflection of the author about his life experiences as a documentary filmmaker and his observations of the dynamics of human relationships. This research was carried out using a qualitative research method or also called a descriptive approach, namely research that is devoted to finding theoretical sources, then analyzing the data, processing and making conclusions. Meanwhile, the source of the research was obtained from listening to speeches written by Arfan Sabran on the TEDx Talks YouTube channel with the title Intergenerational Dialogue & Understanding Humans as the material (TEDx Talks, 2024), and literature from several journals with descriptive analysis and finally an interesting conclusion. This text describes the journey of a documentary filmmaker who was inspired by a simple video of blooming flowers that he and his father watched on television. Initially interested in flora and fauna, the author found his true calling in observing human relationships. He shares his experiences making films that highlight big issues such as deforestation and forest fires, always directing the narrative back to the family. In his documentary works, the author tries to understand the dynamics of intergenerational relationships in the face of environmental and social change. He also described how social media and technology have influenced human interactions, emphasizing the importance of deeper and more harmonious dialogue and communication, by maintaining human connections in order to understand the complex issues faced by modern society.